Definition and Measurement of Children's Emotional and Behavioural Problems “A Review Article - Shennan, Ahmed M. EL-Hassan (Gezira Journal of Educational Sciences and Humanities; مجلد 1 عدد 1 (2004), 2004)
The current literature on children's behaviour problems provides several definitions, primarily the two broad-based categories: emotional (internalizing) and behavioural (externalizing). Although children's emotional and behavioural impairments may be evident at the personal, social, learning, and skills levels, the debate on the influence of culture is at stake. Besides giving general review about these issues the aim of the present paper is to expose the reader to have an idea about how behaviour problems are quantified. The article has also attempted to give an overview of the nature and structure of some of the valid and reliable instruments that are universally employed to measure childhood behavioural deviance.